Safety and Efficacy of Rivaroxaban for Inferior Vena Cava Thrombosis after Successful Catheter-Directed Thrombolysis - Du, Jun; Nie, Menglin; Yan, Zhitong; Fu, Jian; Sun, Jianming; Liu, Fanyun (Seminars in Thrombosis and Hemostasis, 2021)
Rivaroxaban use for inferior vena cava (IVC) thrombosis after successful catheter-directed thrombolysis (CDT) is rarely reported. This study aimed at investigating the safety and efficacy of rivaroxaban for IVC thrombosis after CDT. The clinical data on 38 consecutive patients with IVC thrombosis (68% male; mean age, 51.5 ± 16.5), who received rivaroxaban after CDT between July 2017 and January 2020, were retrospectively analyzed in this study. Safety and efficacy of rivaroxaban (bleedings and recurrent venous thromboembolism), cumulative prevalence of post-thrombotic syndrome (PTS), primary patency, clinically driven target lesion revascularization rate, and other adverse events including all-cause mortality and vascular events (systemic embolism, acute coronary syndrome, ischemic stroke, and transient ischemic attack) were retrospectively analyzed. Of the 38 patients who received rivaroxaban for IVC thrombosis after CDT, 27 (71%) had an anticoagulant duration of 6 months and 11 patients (29%) of more than 6 months. Four patients (10%) suffered recurrent thrombosis. No patient suffered major bleeding, while clinically relevant nonmajor bleeding occurred in two (5%) patients. The cumulative prevalence of PTS was 18% (7/38) during the 12 months follow-up period. Primary patency at 1, 3, 6, and 12 months was 97, 92, 90, and 90%, respectively. According to follow-up data, the clinically driven target lesion revascularization of this study was 10%. Cardiovascular events and mortality did not occur in any patient during the study period. Rivaroxaban for IVC thrombosis after successful CDT can be safe and effective.
Keywords: rivaroxaban; inferior vena cava; thrombosis; catheter-directed thrombolysis; anticoagulation